2017
DOI: 10.1080/03009742.2017.1330419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug survival and clinical outcome in patients with ankylosing spondylitis treated with etanercept or adalimumab

Abstract: No significant difference was found between AS patients treated with etanercept and those treated with adalimumab in mean ASDAS-CRP and reaching ASDAS-CRP minimal disease activity at 2 year follow-up. Drug survival rate was higher in etanercept- compared to adalimumab-treated patients. However, this should be interpreted cautiously as the risk of allocation bias cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Axial spondyloarthritis (axSpA), a chronic inflammatory disease leading to vertebral and sacroiliac fusion, is characterized by lower back pain and back stiffness in the morning 1–3 . Even though there is still no cure for axSpA patients, the application of tumor necrosis factor‐α (TNF‐α) inhibitor in the treatment of axSpA ameliorates the disease status, including controlling the inflammation, decreasing the disease activity, and improving the health‐related quality of life 4–6 . However, the annual cost of TNF inhibitor is high; in addition, a certain proportion of axSpA patients stop the TNF inhibitor therapy because of the lack of efficacy and the presence of adverse events 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA), a chronic inflammatory disease leading to vertebral and sacroiliac fusion, is characterized by lower back pain and back stiffness in the morning 1–3 . Even though there is still no cure for axSpA patients, the application of tumor necrosis factor‐α (TNF‐α) inhibitor in the treatment of axSpA ameliorates the disease status, including controlling the inflammation, decreasing the disease activity, and improving the health‐related quality of life 4–6 . However, the annual cost of TNF inhibitor is high; in addition, a certain proportion of axSpA patients stop the TNF inhibitor therapy because of the lack of efficacy and the presence of adverse events 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…The continuous development and progression of ankylosing spondylitis will eventually lead to spinal fusion and ligamentous ossifications, imposing heavy economic and psychological burdens on patients and their families [3]. In spite of the efforts made in the treatment of ankylosing spondylitis, outcomes are still poor in many patients [4,5]. Ankylosing spondylitis patients are also at high risk of other diseases, such as cardiovascular disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We performed additional subgroup analyses to further compare the clinical effect among different TNF-a inhibitors. A previous study indicated that etanercept and adalimumab treatment led to similar ASDAS-CRP improvement in patients with AS (16). In this study, the ASAS remission rates and HIMRISS were simultaneously compared between etanercept/ infliximab and adalimumab at follow-up time points.…”
Section: Discussionmentioning
confidence: 91%
“…Increasing evidence indicates that early detection and diagnosis of hip inflammation are beneficial to active treatment, which is important to improve hip function and general prognosis of SpA ( 14 ). Tumor necrosis factor (TNF)-α inhibitors are a prompt and robust treatment to improve the signs and symptoms of SpA as well as function and spinal mobility ( 15 , 16 ). In recent clinical studies, TNF-α inhibitors, including etanercept, adalimumab, and infliximab, were shown to be effective for patients with SpA patients with hip involvement in clinical and imaging assessments ( 1 ).…”
Section: Introductionmentioning
confidence: 99%